INVESTIGAÇÃO DAS PROPRIEDADES FOTOCATALÍTICAS DE HETEROJUNÇÕES TIPO BiOBr/FeW𝐎𝟒 NA DEGRADAÇÃO DE POLUENTES - SILVA, Letícia Maria Brito (2023)
Currently, the pollution of water resources is one of the main environmental problems to be tackled in several countries. Therefore, synthetic dyes produced by textile industries, for example, present a problem due to their diverse composition and difficult treatment. In this sense, semiconductors have proven to be a great tool in the photodegradation of organic and inorganic contaminants. Therefore, BiOBr/FeWO4 heterojunctions were synthesized in different compositions of FeWO4, and the photocatalytic properties in the degradation of rhodamine B and methyl orange dyes were investigated. The heterojunctions were characterized by x-ray diffraction, FTIR spectroscopy, Raman spectroscopy, scanning and transmission electron spectroscopy, dispersive x-ray spectroscopy, and diffuse reflectance spectroscopy. The X-ray diffraction pattern for BiOBr was indexed to tetragonal structure. For the heterojunctions, in addition to the diffracted peaks referring to BiOBr, additional peaks were observed, which were attributed to the FeWO4 monoclinic structure, which suggests the existence of the FeWO4 structure in the composition of the heterojunction. The FTIR and Raman spectra showed that in addition to the vibrational modes referring to the BiOBr structure, other vibrational modes were observed, which were attributed to the FeWO4 structure. The SEM images showed a microflower-like morphology for the BiOBr structure, while for the heterojunctions, lamella-shaped structures with small structures on the surface were observed, which were attributed to FeWO4. For the studies of electronic properties, a greater absorption in the visible region was observed in the absorption spectra of the heterojunctions, and similar band gap values for all structures. For the photocatalytic activity of BiOBr/FeWO4 (5,10,15 e 20%) heterojunctions, a greater efficiency of the photocatalytic activity was observed in the degradation of the dye RhB and methyl orange compared to pure BiOBr, with the exception of BiOBr/FeWO4-20% in the degradation of methyl orange, which showed lower degradation. Scavenger tests with iso-propyl alcohol, bezoquinone, showed the existence of oxidative species, namely superoxide and hydroxyl radicals, which directly participate in the photodegradation mechanism of dyes.